2019
DOI: 10.1091/mbc.e18-08-0495
|View full text |Cite
|
Sign up to set email alerts
|

A rapid computational approach identifies SPICE1 as an Aurora kinase substrate

Abstract: Aurora kinases play a major role in mitosis by regulating diverse substrates. Defining their critical downstream targets is important in understanding Aurora kinase function. Here we have developed an unbiased computational approach to identify new Aurora kinase substrates based on phosphorylation site clustering, protein localization, protein structure, and species conservation. We validate the microtubule-associated proteins Clasp2, Elys, tubulin tyrosine ligase-like polyglutamylase residues 330–624 and spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In this respect, we found that serine 612 in BUB-1 is phosphorylated and this serine is embedded in a sequence (RRL S I) closely resembling the consensus for PP2A:B56 reported in Kruse et al, 2020 . Furthermore, the sequence also fits into the loosely defined Aurora B consensus RRxSφ (where φ is a hydrophobic aa) ( Cheeseman et al, 2002 ; Deretic et al, 2019 ; Kettenbach et al, 2011 ). Therefore, BUB-1 itself could be subjected to an Aurora B-PP2A:B56 balance and it will be very interesting to address whether BUB-1 and other meiotic proteins are regulated by the balance between Aurora B and PP2A:B56.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, we found that serine 612 in BUB-1 is phosphorylated and this serine is embedded in a sequence (RRL S I) closely resembling the consensus for PP2A:B56 reported in Kruse et al, 2020 . Furthermore, the sequence also fits into the loosely defined Aurora B consensus RRxSφ (where φ is a hydrophobic aa) ( Cheeseman et al, 2002 ; Deretic et al, 2019 ; Kettenbach et al, 2011 ). Therefore, BUB-1 itself could be subjected to an Aurora B-PP2A:B56 balance and it will be very interesting to address whether BUB-1 and other meiotic proteins are regulated by the balance between Aurora B and PP2A:B56.…”
Section: Discussionmentioning
confidence: 99%
“…Since its identification as a mitotic kinase, research on AURKA has extensively focused on its characterization during mitosis (Barr and Gergely, 2007, Nikonova et al, 2013). Multiple low and high throughput conventional approaches were used to identify mitotic AURKA interactors, which fell short in providing mechanistic insight into the emerging non-mitotic functions of AURKA such as cilium assembly and disassembly (Deretic et al, 2019, Kettenbach et al, 2011, Santamaria et al, 2011). In this study, we overcame this limitation by identifying the proximity interactors of AURKA in asynchronous cells using the BioID approach.…”
Section: Discussionmentioning
confidence: 99%
“…Computational approaches, such as ScanSite (Obenauer, Cantley, & Yaffe, 2003) or PhosphoPredict (Song et al, 2017) have been developed that analyze phosphosites and their motifs and predict potential substrates, such as the prediction and validation of SPICE1 as an Aurora A and Aurora B substrate (Deretic, Kerr, & Welburn, 2019).…”
Section: Techniques In Identifying and Studying Phosphorylationmentioning
confidence: 99%